Green Synthesis of Antimicrobial Silver Nanoparticles using Green Tea Extract: The Role of Concentration and pH - Hasan, Wafiqah Latuapo; Sari, Retno; Hendradi, Esti (JSFK (Jurnal Sains Farmasi & Klinis), 2024)
Silver nanoparticles (AgNP) have been proven effective against many microbial strains with their superior antibacterial  properties, due to their nano size and large surface area that can interact directly with the bacterial structure. Green synthesis  for silver nanoparticles is the process of reducing Ag+ ions to Ag0 using plant bioactive compounds. Green synthesis is safer,  environmentally friendly, and cost-effective. Camellia sinensis L. (green tea) containing polyphenols that can be used as a  bioreductant in the formation of silver nanoparticles. This study aims to determine the effect of various concentration of AgNO3,  green tea extract, and pH on the physical characteristics and antibacterial activity of silver nanoparticles. The AgNPs were  evaluated by UV-Vis Spectrophotometer, Dynamic Light Scattering (DLS), Scanning Electron Microscopy (SEM), and Fourier transform infrared spectroscopy (FTIR). The result demonstrated that the optimal AgNP was obtained from the AgNO3 concentration of 1.5 mM with 0.003% green tea extract at pH 10 which showed the highest absorbance value of 4.420 at λ  435.3 nm, with a particle size of 47.1 nm and a PDI of 0.243. The AgNPs showed growth inhibition on Staphylococcus aureus and  Escherichia coli and the antibacterial activity enhance compare to AgNO3.